More data on ancient human mitogenome variability in Italy: new mitochondrial genome sequences from three Upper Palaeolithic burials. (3rd April 2021) - Modi, Alessandra; Vai, Stefania; Posth, Cosimo; Vergata, Chiara; Zaro, Valentina; Diroma, Maria Angela; Boschin, Francesco; Capecchi, Giulia; Ricci, Stefano; Ronchitelli, Annamaria; Catalano, Giulio; Lauria, Gabriele; et al.
Abstract: Background: Recently, the study of mitochondrial variability in ancient humans has allowed the definition of population dynamics that characterised Europe in the Late Pleistocene and Early Holocene. Despite the abundance of sites and skeletal remains few data are available for Italy. Aim: We reconstructed the mitochondrial genomes of three Upper Palaeolithic individuals for some of the most important Italian archaeological contexts: Paglicci (South-Eastern Italy), San Teodoro (South-Western Italy) and Arene Candide (North-Western Italy) caves. Subjects and methods: We explored the phylogenetic relationships of the three mitogenomes in the context of Western Eurasian ancient and modern variability. Results: Paglicci 12 belongs to sub-haplogroup U8c, described in only two other Gravettian individuals; San Teodoro 2 harbours a U2'3'4'7'8'9 sequence, the only lineage found in Sicily during the Late Pleistocene and Early Holocene; Arene Candide 16 displays an ancestral U5b1 haplotype already detected in other Late Pleistocene hunter-gatherers from Central Europe. Conclusion: Regional genetic continuity is highlighted in the Gravettian groups that succeeded in Paglicci. Data from one of the oldest human remains from Sicily reinforce the hypothesis that Epigravettian groups carrying U2'3'4'7'8'9 could be the first inhabitants of the island. The first pre-Neolithic mitogenome from North-Western Italy, sequenced here, shows more affinity with continental Europe than with the Italian peninsula.